2022
DOI: 10.1002/jat.4285
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to abuse‐like concentrations of toluene induces inflammation in mouse lungs and brain

Abstract: Toluene is an aromatic hydrocarbon commonly abused by young adolescents for its central nervous system depressant effects. Although toluene's pharmacological effects at high concentrations are relatively well-known, few studies have assessed toluene's effects on lung and brain tissues. The present study characterized the pathological effects of acute inhaled toluene exposure in the lungs and brains of male Swiss-Webster mice (N = 68). Using a static vapor exposure chamber, mice (PND 28) received a single 30-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The study, which showed not only the association between exposure to VOCs and increased systemic level of oxidative stress but also the association between markers of oxidative stress and parameters of lung function supports this hypothesis [ 14 ]. As VOCs are gaseous pollutants, their primary target tissue is the lung, and breathing elevated concentrations of VOCs could have direct toxic effects on cells through some possible mechanisms, such as inflammation and DNA repair pathways, in addition to oxidative stress [ 18 , 33 ]. In addition to genetic toxicity, epigenetic mechanisms appear to be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, which showed not only the association between exposure to VOCs and increased systemic level of oxidative stress but also the association between markers of oxidative stress and parameters of lung function supports this hypothesis [ 14 ]. As VOCs are gaseous pollutants, their primary target tissue is the lung, and breathing elevated concentrations of VOCs could have direct toxic effects on cells through some possible mechanisms, such as inflammation and DNA repair pathways, in addition to oxidative stress [ 18 , 33 ]. In addition to genetic toxicity, epigenetic mechanisms appear to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no health studies have looked into how long an accidental single exposure to large amounts of VOCs can affect lung function deterioration. Considering that even low levels of VOCs cause a loss of lung function in the general population [ 13 , 16 ], exposure to very high environmental concentrations of VOCs, albeit acutely, may have long-term adverse effects on lung function decline [ 18 ]. In addition, to the best of our knowledge, there are no children’s studies of a relationship between VOC exposure and lung function.…”
Section: Introductionmentioning
confidence: 99%